The Effects of Feature Sizes in Selectively Laser Melted Ti-6Al-4V Parts on the Validity of Optimised Process Parameters - Phutela, Chinmay (Materials (Basel), 2019)
Ti-6Al-4V is a popular alloy due to its high strength-to-weight ratio and excellent corrosion resistance. Many applications of additively manufactured Ti-6Al-4V using selective laser melting (SLM) have reached technology readiness. However, issues linked with metallurgical differences in parts manufactured by conventional processes and SLM persist. Very few studies have focused on relating the process parameters to the macroscopic and microscopic properties of parts with different size features. Therefore, the aim of this study was to investigate the effect of the size of features on the density, hardness, microstructural evolution, and mechanical properties of Ti-6Al-4V parts fabricated using a fixed set of parameters. It was found that there is an acceptable range of sizes that can be produced using a fixed set of parameters. Beyond a specific window, the relative density decreased. Upon decreasing the size of a cuboid from (5 × 5 × 5 mm) to (1 × 1 × 5 mm), porosity increased from 0.3% to 4.8%. Within a suitable size range, the microstructure was not significantly affected by size; however, a major change was observed outside the acceptable size window. The size of features played a significant role in the variation of mechanical properties. Under tensile loading, decreasing the gauge size, the ultimate and yield strengths deteriorated. This investigation, therefore, presents an understanding of the correlation between the feature size and process parameters in terms of the microscopic and macroscopic properties of Ti-6Al-4V parts manufactured using SLM. This study also highlights the fact that any set of optimized process parameters will only be valid within a specific size window.